Feasibility and Acceptibility of EatSAFE-StopWASTE© Mobile App - Yew Huat Tang, John; Razif Shahril, Mohd (International Journal of Engineering and Technology, 2018)
Food poisoning affects one in six people around the world every year and food wastage due to expired or spoiled food continues to become global problem. It is a hope through the advancement of technology, these issues can be reduced with the help of smartphone apps. The EatSAFE-StopWASTE©  app was developed to be a user friendly, attractive, informative and flexible smartphone app that help users to reduce food poisoning risk through food safety knowledge and food poisoning risk estimator. This app which categorises food into shelf stable food and perishable food aims to reduce food wastage through reminders of the food purchased. The feasibility and acceptability of EatSAFE-StopWASTE© app were tested among 61 respondents, age ranged from 13 to 60 years old. Feasibility and acceptability of the app was found to be at 87.7% and 89.0%, respectively. Respondents agreed that the app is attractive (83.6%), user friendly (90.2%), easy to understand (95.1%), provides good features (82.0%), informative (86.1%), and useful (91.8%). It can be concluded that EatSAFE-StopWASTE© app is highly feasible and acceptable among users as an aid to help them in reducing food poisoning and food wastage.